Refining of glassy materials with aluminium compounds nano-molecules - Drajewicz, Marcin; Wasylak, Jan (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
A new technology of refining soda-calcium-silicon glassy surfaces with aluminium compounds nano-molecules has been shown in the present study. A structural definition of aluminium compounds nano-powders exposed to thermal processing, including grain-size analysis, has been discussed. Optimal technical and technological parameters of the refining process have been selected. The method of refining soda-calcium-silicon glassy surfaces with aluminium compounds nano-molecules ensures profitable operational properties of the glass, such as increased bending strength, scratching resistance, micro-hardness and chemical resistance without deterioration of the optical properties. Nano-molecules were spread onto the heated glass surface, or onto the cold glass surface and then heated up to temperatures close to the glass transformation, when nano-molecules penetrate into the glass surface. Testing results of the glass operational properties, such as bending strength, scratching resistance, micro-hardness, chemical resistance and optical properties have been presented. The received results develop new possibilities with respect to opaque glass, float glass and glass fibres, as well as to glass processing.
Optica Applicata, Vol. 38, 2008, nr 2, s. 421-430
Keywords: optyka; glass; nano-molecules; aluminium powder; refining